2022
DOI: 10.3389/fpsyg.2022.1003866
|View full text |Cite
|
Sign up to set email alerts
|

Curious enough to start up? How epistemic curiosity and entrepreneurial alertness influence entrepreneurship orientation and intention

Abstract: Epistemic curiosity as the desire to acquire new knowledge and ideas is considered as an important attribute for successful entrepreneurs among practitioners, yet there is lacking empirical evidence of epistemic curiosity having an effect on entrepreneurial outcomes. This study aims to put a spotlight on epistemic curiosity as a predictor for entrepreneurial intentions and orientation. We found that epistemic curiosity has a stronger influence on entrepreneurial outcomes in comparison to the Big Five personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 106 publications
(160 reference statements)
0
5
0
Order By: Relevance
“…The research is limited to the personality characteristics of persons and the sociological entrepreneurial background as an important set of factors that can contribute to the establishment of companies. Other factors that might be important for the setting up of companies (e.g., innovativeness, Alshebami and Seraj, 2022 ; creativity, Peljko and Auer Antončič, 2022 ; narcissism and resilience, Leonelli et al, 2022 ; improvisation, Guo et al, 2022 ; emotional intelligence, Lopez-Nunez et al, 2022 ; epistemic curiosity and entrepreneurial alertness, Heinemann et al, 2022 ; financial rewards and social recognition, Ismail, 2022 ; theory of planned behavior components: personal attitude, subjective norms, and perceived behavioral control, Maheshwari, 2021 ) were not included in the research and can be added in future studies.…”
Section: Limitations and Future Research Possibilitiesmentioning
confidence: 99%
“…The research is limited to the personality characteristics of persons and the sociological entrepreneurial background as an important set of factors that can contribute to the establishment of companies. Other factors that might be important for the setting up of companies (e.g., innovativeness, Alshebami and Seraj, 2022 ; creativity, Peljko and Auer Antončič, 2022 ; narcissism and resilience, Leonelli et al, 2022 ; improvisation, Guo et al, 2022 ; emotional intelligence, Lopez-Nunez et al, 2022 ; epistemic curiosity and entrepreneurial alertness, Heinemann et al, 2022 ; financial rewards and social recognition, Ismail, 2022 ; theory of planned behavior components: personal attitude, subjective norms, and perceived behavioral control, Maheshwari, 2021 ) were not included in the research and can be added in future studies.…”
Section: Limitations and Future Research Possibilitiesmentioning
confidence: 99%
“…Risk is defined as the probability of a substantial financial loss, but the same dollar amount of possible loss could be more severe for one entrepreneur than another (Sonfield and Lussier, 2000). While risk may also involve non-financial threats like damage to reputation, it is our view that high risk seen as a threat among immigrants may arouse their own epistemic curiosity (i.e., desire for knowledge that motivates individuals to learn new ideas, eliminates information gaps, and solves intellectual problems : Heinemann et al, 2022). Generally, risk perception has been conceptualized as an assessment of risk by the decision-maker in a given situation (Mullins and Forlani, 2005).…”
Section: Perceived Risk and Immigrant Entrepreneurship Intention (Iei)mentioning
confidence: 99%
“…Similarly, individuals with low-risk tolerance may be more likely to avoid entrepreneurial activities and seek out traditional employment opportunities [79]. Entrepreneurial alertness refers to a person's ability to recognize and identify entrepreneurial opportunities [80,81]. Research has shown that individuals with higher entrepreneurial alertness are most likely to be engrossed in entrepreneurial activities and pursue entrepreneurial opportunities [82,83].…”
Section: Personality Traitsmentioning
confidence: 99%